Peran Masyarakat Lokal dalam Mengelola Kerusakan Lingkungan untuk Mengatasi Konflik Sosial - Herdiansyah, Herdis; Vitiara, Mustarini Dessy; Frimawaty, Evi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Environmental damage from palm oil production remains a pressing and significant global issue, driving ecosystem disruption and social conflicts. Local communities, as the first to experience its impacts, are central actors in addressing deforestation, pollution, and biodiversity loss. This study examines the role of local communities in the Subah sub-district, Indonesia, in managing environmental degradation and mitigating social conflicts associated with palm oil plantations. A mixed-methods approach was employed, combining a Likert scale questionnaire with 101 respondents and field observations to capture both quantitative trends and community perspectives. The study underscores the importance of empowering local communities by integrating their traditional knowledge and practices into broader environmental governance frameworks. Over 60% of respondents agreed that active participation improves environmental quality and reduces conflict, with nearly 70% reporting direct involvement in conflict resolution. For instance, community-led reforestation in Sabung Village restored biodiversity and strengthened social cohesion, while waterway cleanups in Mukti Raharja Village reduced pollution and eased tensions with plantation companies. These examples highlight how grassroots initiatives can foster both ecological restoration and social harmony. This study’s novelty lies in its focus on community driven environmental practices as dual strategies for ecological management and peacebuilding in palm oil-producing regions. The results suggest the need for participatory approaches, where companies collaborate with communities to promote sustainable practices, prevent environmental degradation, and ensure long-term social stability.